Intestinal Transport of 3,6′-Disinapoylsucrose, A Major Active Component of Polygala tenuifolia, Using Caco-2 Cell Monolayer and In Situ Rat Intestinal Perfusion Models - Chen, Ying; Liu, Xinmin; Pan, Ruile; Zhu, Xiaoxin; Steinmetz, André; Liao, Yonghong; Wang, Ning; Peng, Bo; Chang, Qi (Planta Medica, 2013)
3,6′-Disinapoylsucrose is a major active component of the herb Polygala tenuifolia which has long been used for relieving tranquilization, uneasiness of the mind, and improving learning and memory. Our previous study found that 3,6′-disinapoylsucrose had a very low oral bioavailability. Its mechanisms of absorption in the small intestine have so far been unclear. In the present study, the absorption mechanisms of 3,6′-disinapoylsucrose were investigated by using the Caco-2 cell monolayer and in situ rat intestinal perfusion models. The 3,6′-disinapoylsucrose concentration was determined by an LC/MS/MS method. In a Caco-2 cell transport study, the results showed that 3,6′-disinapoylsucrose had very limited intestinal permeability with average apparent permeability coefficient values around (1.11–1.34) × 10−7 cm/s from the apical (A) to the basolateral (B) side and (1.37–1.42) × 10−7 cm/s from B to A, at concentrations of 5, 20, and 33 µM. No concentration dependence in the 3,6′-disinapoylsucrose transport was observed. The apparent permeability coefficient value of 3,6′-disinapoylsucrose (5 µM) from A to B greatly increased to 4.49 × 10−7 and 1.81 × 10−7 cm/s, respectively, when the cells were preincubated with EDTA (17 mM) and sodium caprate (5.14 mM). No significant effect on the 3,6′-disinapoylsucrose transport by the inhibitors including verapamil, cyclosporine A, and sodium azide was observed. Similar results were found in the small intestinal perfusion study. The apparent permeability coefficient value of 3,6′-disinapoylsucrose greatly increased from 3.97 × 10−6 to 23.4 × 10−6 and 20.0 × 10−6 cm/s in the presence of EDTA (17 mM) and sodium caprate (5.14 mM), respectively, in perfusion buffer. An in vitro stability evaluation of 3,6′-disinapoylsucrose in the gastrointestinal tract showed that it was relatively stable both in the stomach and small intestine contents, while it was found to be more instable in the colon contents. All of the above results indicate that 3,6′-disinapoylsucrose might be transported across the intestinal mucosa by paracellular passive penetration and paracellular enhancers could increase the intestinal permeability of this compound and thus slightly improve its oral bioavailability.
Keywords: 3,6′-disinapoylsucrose; Polygala tenuifolia; Polygalaceae; Caco-2 cell; intestinal perfusion; absorption enhancer